Mannose binding lectin and prediction of risk for chemotherapy induced febrile neutropenia in patients with a solid tumor. (16th March 2019) - Epskamp, Cynthia; Goudzwaard, Jeannette A.; Fiets, Edward; Zuetenhorst, Johanna M.; Polee, Marco B.; van de Geijn, Gert-Jan M.; van Schaik, Ron H.N.; Birnie, Erwin; Hamberg, Paul
Abstract: Mannose-binding lectin (MBL) - deficient patients who undergo chemotherapy for a solid tumor might have an increased risk developing febrile neutropenia (FN). We investigated in a prospective cohort study relations between MBL-serum levels and polymorphisms in MBL promotor genotypes (−550H/L and −221X/Y) on incidence and severity of FN. Risk of FN was 17.9% in MBL-deficient and 22.5% in MBL-sufficient patients (RR = 0.796, p = 0.45). Median MBL serum levels at baseline were respectively 1.39 µg/mL and 1.09 µg/mL ( p = 0.92) in patients with and without FN. In conclusion, serum MBL and MBL genotypes (−550H/L and −221X/Y) do not determine the risk for developing FN.